2010
DOI: 10.3791/1991
|View full text |Cite
|
Sign up to set email alerts
|

Cell Electrofusion Visualized with Fluorescence Microscopy

Abstract: Cell electrofusion is a safe, non-viral and non-chemical method that can be used for preparing hybrid cells for human therapy. Electrofusion involves application of short high-voltage electric pulses to cells that are in close contact. Application of short, high-voltage electric pulses causes destabilization of cell plasma membranes. Destabilized membranes are more permeable for different molecules and also prone to fusion with any neighboring destabilized membranes. Electrofusion is thus a convenient method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, treatment with PEG showed toxic effects on cells and therefore we continued only with Syncytin1 overexpression for further experiments. We then tested electrofusion – the use of high voltage electrical pulses to induce fusions of cells in close proximity 60 – on an admixture of the cells expressing either halve. For this aim, different voltages were tested: 300V 500 µs one pulse vs 700V 15 µs three pulses.…”
Section: Resultsmentioning
confidence: 99%
“…However, treatment with PEG showed toxic effects on cells and therefore we continued only with Syncytin1 overexpression for further experiments. We then tested electrofusion – the use of high voltage electrical pulses to induce fusions of cells in close proximity 60 – on an admixture of the cells expressing either halve. For this aim, different voltages were tested: 300V 500 µs one pulse vs 700V 15 µs three pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, other research groups performed similar electrofusion studies using mouse melanoma cells (B16-F1) and mouse embryonic cells. The results showed that the optimal electric field intensity values were 1200 V/cm [35] and 800 V/cm [36] , respectively. According to the previous studies, there is a slight difference in optimal electric field intensity in different cells.…”
Section: Cell Fusionmentioning
confidence: 99%
“…The Zimmermann group suggested that the pulse duration should not exceed 100 μs, otherwise it would cause irreversible electroporation, resulting in cell lysis. In recent years, microsecond (μs)-level pulses have been widely applied in cell electrofusion experiments [35,36] . Nevertheless, the microsecond-level pulse duration is still relatively long and will lead to a large electroporation radius, causing serious irreversible damage to the cell membrane and ultimately resulting in a significant decrease in cell fusion yield.…”
Section: Cell Fusionmentioning
confidence: 99%
“…For treatments using hypoosmolar buffer, a wash step using isoosmolar buffer prior to PEG treatment was used. Isoosomolar potassium phosphate buffer (10 mM KH2PO4, 10 mM K2HPO4, 1mM MgCl2, and 250 mM sucrose, in dH2O) and hypoosmolar potassium phosphate buffer (10 mM KH2PO4, 10 mM K2HPO4, 1mM MgCl2, 75 mM sucrose, in dH2O) were prepared as previously described [22], filter-sterilized, and stored at 4°C before use. Every treatment was replicated four times, with 1 to 3 wells each time.…”
Section: Homokaryon Productionmentioning
confidence: 99%